1957
DOI: 10.1063/1.1743938
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Diffusion of Hydrogen on Nickel

Abstract: The surface diffusion and adsorption of hydrogen on Ni field emitters has been investigated by a technique previously used for similar studies of H and O diffusion on W. It was found that diffusion occurs with an activation energy of 7±1 kcal in the chemisorbed layer, without the precipitation boundaries observed on W. This is believed to result from the inherent homogeneity of f.c.c. substrates, on which most adsorption sites seem equivalent. This is supported by the marked lack of emission anisotropy of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…There is some evidence from other experiments that the adsorbed hydrogen is atomic. [6][7][8] These three conclusions are consistent with some simple observations made from the models of Figure 2. Each atom in the body of a face-centered cubic crystal is tot4,/ tihasssst sh-,X 2; o In the se renu(or drim) adsorption, one oe thattheX rearrange ( 1 10) ice surface P<l X 1) or (1 X 1).…”
supporting
confidence: 85%
“…There is some evidence from other experiments that the adsorbed hydrogen is atomic. [6][7][8] These three conclusions are consistent with some simple observations made from the models of Figure 2. Each atom in the body of a face-centered cubic crystal is tot4,/ tihasssst sh-,X 2; o In the se renu(or drim) adsorption, one oe thattheX rearrange ( 1 10) ice surface P<l X 1) or (1 X 1).…”
supporting
confidence: 85%
“…Ns, CH4, C2H6, CsH8 on silica-alumina 1 Gabor (1959, 1960) S02, CO,, NHS, í-C4Hi", C2H4 on Vycor glass 1 Perkinson (1965); Russell (1955); Gilliland, et al (1958Gilliland, et al ( , 1974 CJb'sCls, S02 on silica powder 1 Carman (1956); Carman and Raal (1957) H-Pt 3 This study O-W, H-W, H-Ni 3 Gomer and Hulm (1957); ; Wortman, et al (1957) Cs-W, Ba-W 2 Taylor and Langmuir (1933); Drechsler (1954) Ar-W, 02-0/W" COs-COs/W" 1 Gomer (1958Gomer ( , 1959; Gomer and Hulm (1957) °This refers to surface migration of a physically adsorbed layer on top of a chemisorbed layer.…”
Section: Correlation Of Surface Diffusivitiesmentioning
confidence: 94%
“…They found that the total amount of hydrogen liberated at this temperature was approximately 0.0001 percent. Wortman et al, [255], reported that the diffusion of hydrogen Figure 32. Variation of diffusion rate of hydrogen in nickel with temperature [253'\. Grimes [258] observed that deformations up to 10 percent caused no significant change in the diffusion coefficient for hydrogen through unstrained nickel, which he gave as 0.0095 exp (~10,S00/RT) cm-' sec.…”
Section: Totalmentioning
confidence: 99%